The comparison of position-specific match performance between the group and knockout stage of the UEFA Champions League - Šunjic, I.; Versic, S.; Modric, T.; Corluka, M.; Zaletel, P. (SportMont, 2024)
This study aimed to compare match performance in the group and knockout stage of the UEFA Champions League (UCL) for players in different playing positions. The information on physical and technical performances was collected during all UCL matches (n=125) in the 2022/23 season. Players` observations (n=1387) were classified according to their playing positions as central defender (CD; n=471), fullback (FB; n=283), central midfielder (CM; n=376), winger (WM; n=137) and forward (FW; n=104). No differences in technical performance between the group and knockout stage were found for CDs, FBs, CMs, and WMs, while only FWs achieved significantly less shots on target (Cohen`s d (d=0.46), total passes (d=0.54), successful passes (d=0.49), and more duels (d=0.39) in the knockout compared to the group stage. The CDs, CMs, and WMs covered greater distance at moderate (d=0.46-0.63) and high (d=0.29-0.38) speeds in the knockout compared to the group stage, while no differences in physical performance between the group and knockout stage were found for FBs and FWs. This study demonstrated that (i) the technical performance of UCL players was in general stable irrespective of the competition stage, (ii) matches played in the knockout stage were characterized by greater match intensity compared to the matches played in the group stage of UCL for CDs, CMs, and WMs. These findings may help football coaches in the decision-making process when selecting the players for specific matches and designing training programs.